ANALISIS RIWAYAT BERAT BADAN LAHIR RENDAH (BBLR) DENGAN PERKEMBANGAN ANAK USIA BALITA: SISTEMATIC LITERATURE REVIEW - Artiyan Agi Wibiyani; Erni Gustina (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2021)
The prevalence of low birth weight (LBW) is 15% of all births in the world and mostly occurs in developing countries. Based on statistical analysis shows that 90% of LBW events occur in developing countries and the mortality rate reaches 35 times compared to babies born with normal weight. Long-term problems that can occur in children who have a history of LBW include growth and development. The purpose of the study was to determine the relationship between a history of LBW and the development of children under five. Systematic literature review was used in this study. The search strategy used 2 electronic databases, namely PubMed and Google Scholar and followed the PRISMA (Prefferes Reporting Items For Systematic Review And Meta Analyses) protocol, with a publication period of 2011-2020. There were 18 articles that matched the inclusion and exclusion criteria. The results of the study of research articles found that there was a relationship between a history of LBW and the development of children under five. The paper discusses development that includes gross motor, fine motor, speech and language development, as well as social and independent development. Based on the article review, besides being caused by low birth weight, development can also be influenced by several other factors including parental stimulation, nutrition, and the sex of the child. Children with a history of LBW are at greater risk of experiencing slower growth and development than infants with normal weight. The impact is the failure to grow and develop according to age. Families with babies who have a history of LBW are expected to always provide more optimal health efforts by utilizing health service facilities so that children can grow and develop properly.Abstrak dibuat maksimal terdiri dari 200 kata, meliputi tujuan, metode, hasil, pembahasan dan kesimpulan dilakukannya penelitian. Abstrak tidak boleh berisi tabel/gambar, tidak perlu mencantumkan sitasi.  Hindari singkatan seminimal mungkin. (font: Times New Roman 10, cetak normal, posisi rata kanan kiri, bahasa latin dengan cetak miring, berbahasa Inggris).